2018
DOI: 10.1080/15257770.2018.1498516
|View full text |Cite
|
Sign up to set email alerts
|

DNA methyltransferases expression in normal tissues and various human cancer cell lines, xenografts and tumors.

Abstract: View related articles View Crossmark data Citing articles: 8 View citing articles DNA methyltransferases expression in normal tissues and various human cancer cell lines, xenografts and tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…DNMT1 expression can be downregulated by RX-3117, which affects DNA methylation. DNMT1 shows a large variation in expression in various cancer cell lines, human xenografts and human tumor tissues [48]. This can easily be measured using either PCR or immunohistochemistry, both in tumor tissue and normal cells such as white blood cells.…”
Section: Dna Methyltransferasesmentioning
confidence: 99%
“…DNMT1 expression can be downregulated by RX-3117, which affects DNA methylation. DNMT1 shows a large variation in expression in various cancer cell lines, human xenografts and human tumor tissues [48]. This can easily be measured using either PCR or immunohistochemistry, both in tumor tissue and normal cells such as white blood cells.…”
Section: Dna Methyltransferasesmentioning
confidence: 99%
“…Other studies reported association of this polymorphism with global methylation levels of leukocyte DNA [31], with MTHFR methylation levels in blood DNA of valproate-treated patients with epilepsy [32], and with hypermethylation of tumor suppressor genes in cancer specimens [33] or adjacent healthy tissues [17]. The present finding of a correlation between the MTR 2756A > G polymorphism and DNMT1 promoter methylation levels in blood DNA not only strengthens the contribution of this genetic variant to the DNA methylation levels in leukocytes, but it could also be of relevance for those disorders, such as hematological malignancies, autoimmune/inflammatory disorders, and solid tumors, that are linked to impaired DNMT1 methylation and/or expression [5][6][7][8][9][10][11][12]. For example, changes in DNMT1 methylation levels were observed in peripheral blood DNA samples from ALL patients [8], the MTR 2756A > G polymorphism was linked to the risk of pediatric ALL [34], and several maternal polymorphisms of the MTR gene were recently proposed as responsible of aberrant methylation of ALL-related genes in their offspring [35].…”
Section: Discussionmentioning
confidence: 64%
“…As discussed above, DNMT1 is the main enzyme responsible for the maintenance of DNA methylation during cell division, and previous studies revealed the existence of a CpG island in the promoter/5' untranslated region (5'UTR) of the DNMT1 gene itself, whose methylation levels regulate DNMT1 gene expression in both healthy and pathological tissues [5][6][7][8][9][10][11][12]. In this regard, increased DNMT1 promoter methylation resulting in decreased gene expression levels was observed in blood DNA of individuals with ankylosing spondylitis, a chronic inflammatory autoimmune disease [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations